Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China - Chen, Zhi-Teng (Zootaxa, 2020)
Sinoperlodes zhouchangfai gen. nov., sp. nov. is described and illustrated on the basis of male and female adults from Tianmu Mountain, Zhejiang Province of southeastern China, representing the first record of subfamily Perlodinae in coastal southeastern China. The new genus is characterized by extremely complicated netlike venation on apical half of wings; an entire, moderately elevated tergum 10 of male which with small transverse membrane and posteriorly covered with sensilla basiconica and sharp spines; seven small apical lobes of aedeagus; short elliptical eversible paraproct lobes and banded legs. Female of the new genus is distinctive with an elongated, broad subgenital plate covering sternum 9.